2021
DOI: 10.1155/2021/9524143
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tear Ferning Patterns in Young Female Subjects with Refractive Errors

Abstract: To evaluate the dry eye symptoms and ocular tear film in young female subjects with refractive errors (RE) using the ocular surface disease index (OSDI), phenol red thread (PRT) and tear ferning (TF) tests. Methods. A group of 50 young female subjects (mean ± standard division = 20.3 ± 1.1 years) with RE (−0.25 to −6.00D) completed the study. An age-matched control group consisting of 50 healthy normal eye female subjects (22.2 ± 1.5 years) was recruited for comparison. The OSDI was completed first, followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 53 publications
(45 reference statements)
2
11
0
Order By: Relevance
“…As such, the association between dry eye and smoking has been clearly established. The median OSDI score in the current study was comparable to those reported for smokers and subjects with a high body mass index [ 18 , 47 ], but lower compared with the OSDI scores for subjects with diabetes and refractive errors [ 48 50 ].…”
Section: Discussionsupporting
confidence: 73%
“…As such, the association between dry eye and smoking has been clearly established. The median OSDI score in the current study was comparable to those reported for smokers and subjects with a high body mass index [ 18 , 47 ], but lower compared with the OSDI scores for subjects with diabetes and refractive errors [ 48 50 ].…”
Section: Discussionsupporting
confidence: 73%
“…Dry eye symptoms are experienced by 5 to 35% of the world population 5 . Dry eye can be diagnosed using the Schirmer, 6 phenol red thread, 6 noninvasive tear breakup time, 7 tear meniscus height, 8 osmolarity, 9 tear evaporation rate, 10 and tear ferning 11 tests along with the use of questionnaires 12 …”
mentioning
confidence: 99%
“…4 Dry eye symptoms are experienced by 5 to 35% of the world population. 5 Dry eye can be diagnosed using the Schirmer, 6 phenol red thread, 6 noninvasive tear breakup time, 7 tear meniscus height, 8 osmolarity, 9 tear evaporation rate, 10 and tear ferning 11 tests along with the use of questionnaires. 12 Cigarettes contain many toxic chemicals (hydrocarbons, methanol, aldehydes, nitrosamines, carbon monoxide, and heavy metals) that cause damage to nucleic acids, proteins, and lipids.…”
mentioning
confidence: 99%
“…A digital microscope (Olympus DP72; Tokyo, Japan) was used to observe and capture the TF patterns at a magnification of 10×. The TF patterns for each tear sample were graded based on the five-point TF grading scale (from 0 to 4), using increments of 0.1 [28][29][30][31][32]. Dry eye was defined for a TF grade � 2.…”
Section: Tf Testmentioning
confidence: 99%